Fulfillment of Children's Rights During in the Prison - Nyi R. Irmayani (Asian Social Work Journal, 2018)
The fulfillment of children's rights in the family and community affects children's growth and development. However, children can be trapped in actions that harm others or contrary to existing norms. The child under these conditions will face the law and must follow the legal process. During the child undergoes the legal process is detained along with the adult prisoners but in separate cell. This study aims to determine the physical and psychological conditions, the fulfillment of children's rights, and facilitating to the child while in prison. Qualitative research method with case study approach will answer the purpose. The results showed that children who are waiting for the trial process between the ages of 13 to 17 years are placed in one cell as many as 5 children with the condition of the cells of concern. While in the prison less fulfills the rights of children such as health, education, protection or health care. Assistance to such children is only done by the correctional social work of the Correctional Institution.